Scotland ' s approach to forensic mental health and learning disabilities – the Forensic Network. (14th December 2015) - Walker, Helen; Murphy, Lesley; Gration, Vivienne
Abstract : Purpose: – The Forensic Mental Health Services Managed Care Network is described, including the School of Forensic Mental Health. The purpose of this paper is to outline background, it details successes and challenges, focuses on links to clinical practice for Learning Disabilities (LD) service development, describes education and training, multi-disciplinary and multi-agency working and quality improvement. Findings from a small scale brief educational study undertaken in the high-secure service are included as an example of good practice. Design/methodology/approach: – Specific features relating to LD are highlighted. Comparisons are made with other managed clinical and managed care networks. Findings: – The Forensic Network has evolved over time. It has played a crucial role in shaping Scotland's approach to Forensic Mental Health and LD. Central to its success is active involvement of key stakeholders, a multi-agency approach and collaborative working practice. Future plans include formal evaluation of impact. Originality/value: – This paper offers an interesting perspective from a forensic mental health managed care network; the existing literature is limited.